Complication of intraprosthetic dislocation of dual-mobility hip implant following closed reduction. (22nd March 2018) - Mukundu Nagesh, Navin; Patel, Nimesh; Howell, Jonathan
Abstract : Total hip replacement is a successful operation for the management of hip pain but there are potential complications, of which dislocation is one of the most common. The management of recurrent dislocation is a challenging problem that requires a multimodal approach and the use of dual-mobility implants is one option. We present a patient who was previously revised with a dual-mobility implant for recurrent dislocation, who had a complication after closed reduction of a subsequent intraprosthetic dislocation. Following a missed radiographical diagnosis, the patient experienced mechanical symptoms on hip flexion caused by a disassociated dual-mobility implant. Subsequent surgical removal of the failed implant and revision was required. Careful study of radiographs revealed an eccentric femoral head and evidence of the disassociated implant within the surrounding soft tissues. Radiographs following closed reduction of intraprosthetic dislocations should be scrutinised closely to detect implant failure to prevent further complications.